The New Forms of Social Exclusion - Sara Palermo; Rosalba Morese (IntechOpen, 2019)
This is the first book that broadly delves into the theme of social exclusion and how it has changed through culture and society. It represents a very important, innovative, and current attempt to describe new forms of social exclusion in society and takes into account the contribution of different disciplines with different points of view. The authors offer a very interesting and novel contribution to the field of new forms of social exclusion, reporting their theoretical perspectives, the original results of their research, and their discussions. ""Exclusion is always dangerous. Inclusion is the only safety if we are to have a peaceful world."" Pearl S. Buck
English
Keywords: Social Sciences; Social Sciences and Humanities; Social Psychology